2021
DOI: 10.3390/atmos12060743
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Air Pollution before, during and after the COVID-19 Pandemic Lockdown in Nanjing, China

Abstract: A unique illness, the coronavirus disease 2019 (COVID-19), emerged in Wuhan, People’s Republic of China, in December 2019. To reduce the spread of the virus, strict lockdown policies and control measures were put in place all over the world. Due to these enforced limitations, a drastic drop in air pollution and an improvement in air quality were observed. The present study used six air pollutants (PM10, PM2.5, SO2, NO2, CO and O3) to observe trends before, during and after the COVID-19 lockdown period in Nanji… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 47 publications
4
17
0
Order By: Relevance
“…Although the trajectories do not originate directly from the continent, the prevailing northeasterly winds associated with the eastward-propagating anticyclone from the Taiwan Strait make it possible to inject long-range transported pollutants into Taiwan. In addition, as the lockdown measures and travel restrictions of neighboring major cities were gradually lifted in early April for economic recovery, an apparent rebound effect was detected ( Gao et al, 2021 ; Hasnain et al, 2021 ), and trajectories of polluted air masses to central Taiwan were observed originating from neighboring major cities ( Wu and Huang, 2021 ). When the prevailing northeasterly wind is obstructed by the Central Mountain Range, low wind speeds and strong subsidence occur over the leeside of the mountain, often leading to serious PM 2.5 accumulations in central and southern Taiwan.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Although the trajectories do not originate directly from the continent, the prevailing northeasterly winds associated with the eastward-propagating anticyclone from the Taiwan Strait make it possible to inject long-range transported pollutants into Taiwan. In addition, as the lockdown measures and travel restrictions of neighboring major cities were gradually lifted in early April for economic recovery, an apparent rebound effect was detected ( Gao et al, 2021 ; Hasnain et al, 2021 ), and trajectories of polluted air masses to central Taiwan were observed originating from neighboring major cities ( Wu and Huang, 2021 ). When the prevailing northeasterly wind is obstructed by the Central Mountain Range, low wind speeds and strong subsidence occur over the leeside of the mountain, often leading to serious PM 2.5 accumulations in central and southern Taiwan.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…As per Lal et al, 2000, O3 is a negligible pollutant that is released from sunlight and nitrogen oxides (NOx) and volatile organic compounds (VOCs). A decreasing trend in O3 was observed pre lockdown phase, while during the lockdown, O3 showed an increasing tendency was also observed by Hasnain et al, 2021 at China due to the enhancement of solar radiation in the summer, because of the emissions of isoprene and biomass burning (Lu et al, 2018). As per Islam et al 2020, O3 increased during the lockdown phase in Bangladesh, and Mahato et al 2020 found the same in Delhi, India.…”
Section: Discussionmentioning
confidence: 95%
“…CO is mainly a colorless gas emanated from biofuel burning, vehicular emission, agricultural waste burning, and combustion of fossil fuels (Hasnain et al, 2021). Figure 2 shows the concentration pattern of CO, and variations in CO are presented in Tables 1-3.…”
Section: Carbon Monoxidementioning
confidence: 99%